O movimento Open Access em universidades públicas brasileiras: uma reflexão crítica sobre as estratégias de reconstrução da comunicação organizacional e científica na cibercultura - Nascimento, Gesialdo Silva do (2017)
This Dissertation presents reconstruction process happened in cyberculture, which is associated to organizational communication and scientific communication. In this way, both of them work Open Access strategies in a hybrid way. Besides, they were chosen as an approach to understand social and political meaning of studied subject. In fact, this argumentation is concentrated on Universidade de São Paulo (USP) which has implanted in its practices necessary platforms to use this method. The social and glocal interaction within its basis allows along with information and communication technologies to model ecosystem, community and acting networks, which consist of world and lifestyle alteration factor. Actuation webs which are originated make possible that the intelligence must be developed or enhanced collectively by an organic and cybernetical interconnection. Along these lines, the speech is featured to promote new actuation manners. The machine-man is the language and image which are introduced in culture and has in the theory developed by authors like: Virilio, Trivinho, Rüdiger and Lévy. They end up being incorporated by public. In this study, research methodologies include corpus analysis, speech analysis, case study and exploratory research which search for checking customs changes as well as sociability phenomenon. There is a clear criticism relied on capitalism business standard which supports our society as if it were a war engineering designed to defense. Nowadays, this conception is applied by collectivity in order to perform its activities with a view to improve life conditions, education, competition, abilities and crucial individual conviviality as social inset. A cultural transformation rises up cyberspace possibilities which bring about vectors and inventions as communication and control foundation in a transformed society. This type of society which promotes and suffers changes is also characterized by free information flow, people outflow and goods flux. These different sorts of courses demand decoding meanings in current speed in order to figure out a neologism outbreak and its definition known as biocommunication